0304 Greater Slow-Wave Activity is Associated with Deteriorating Mood Across Sleep Restriction. (27th May 2020) - Larson, O R; Jones, C W; Basner, M; Dinges, D F
Abstract: Introduction: Mood progressively deteriorates over consecutive days of sleep restriction. The neurobiological processes active during sleep that influence the risk of mood disturbance are unknown. This study investigated the relationships between physiological sleep parameters (i.e., slow-wave activity (SWA), slow-wave energy (SWE), rapid eye-movement (REM) sleep duration and latency), and self-reported measures of mood across sleep restriction. Methods: N=181 healthy participants (48.1% female; 30±6.8 yrs) had valid polysomnography (PSG) and mood data. The study design included two baseline nights (8h time in bed [TIB]) followed by five nights of 4h TIB. PSG (EEG derivations C3-A2, Fz-A1, O2-A1) was collected on the second baseline night (B2), first night of 4h TIB (SR1), and the fifth night of 4h TIB (SR5). The Profile of Mood States was assayed on days following PSG. Power spectral analysis for SWE and SWA was conducted (delta power; band: 0.5-4.5 Hz). General linear regression models were used to independently assess the slope of SWE, SWA, percent REM of total sleep time (TST), and REM latency on mood disturbance across sleep restriction. Results: At baseline, higher SWE (unadjusted; r=0.21; P=0.004) and SWA (unadjusted; r=0.19; P=0.007) were associated with greater mood disturbance; these relations were attenuated when adjusted for age and sex. No relation was found between mood and REM latency or REM percent of TST. The slope of mood disturbance from B2 to SR5 was associated with greater percentage increases in C3 SWA on SR5 relative to B2 (β=0.039; P=0.008); this association was not observed for SWE (β=-0.016; P=0.48). The slope of REM latency and REM percent of TST were not associated with the slope of mood disturbance. Conclusion: Our results indicate that greater SWA due to sleep restriction was associated with greater mood disturbance, suggesting that less SWA may confer resilience to mood disturbances resulting from sleep restriction. Support: This work was supported by National Institute of Health NIH R01NR004281 and National Space and Biomedical Research Institute NSRBI NCC 5-98.